HUBUNGAN PENGETAHUAN LINGKUNGAN TERHADAP PERILAKU RAMAH LINGKUNGAN MAHASISWA STKIP YDB LUBUK ALUNG - Reni Nastuti; Lelfita Lelfita (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2020)
Massive and increasingly complex environmental issues are becoming important and urgent to further address environmentally friendly behaviors, at every level of society, including students, so that environmental problems can be resolved. This research aims to examine the relationship of environmental knowledge to the environmentally friendly behavior of STKIP YDB Student Lubuk Alung. Because there is still a lack of environmentally friendly behavior among students. The respondents in this study were students who had taken IAD courses and came from Adiwiyata school. The instruments used in this study are questions and questionnaires. The method used in this study is a descriptive method with product moment correlation data analysis technique. The results said that students had high knowledge of the environment ,where 85% of respondents had scores in the range of 97-75 and had low environmentally friendly behaviors, this was shown by the data of environmentally friendly behavior polls, where30% of respondents always behaved environmentally both on campus and at home. Based on the analysis of environmental knowledge relationship data to environmental behavior. it found that t count was 0.6819 and t table of 1,658 at a significant rate of 5% and the results stated there was no relationship of environmental knowledge to environmentally friendly behavior.